GP108 National pews implementation in ireland; outlining the experience of implementing a mandated paediatric patient safety improvement initiative. (June 2019) - MacDonell, Rachel; Horkan, Siobhan; Fitzsimons, John; Nicholson, Alf
Abstract : Background: The Irish Paediatric Early Warning System (I-PEWS) and associated National Clinical Guideline No.12 was developed in response to a ministerial mandate as a funded workstream of the National Clinical Programme for Paediatrics. I-PEWS is a multifaceted approach to improving patient safety and clinical outcomes, based upon the implementation of several complementary interventions, including 5 age-specific paediatric observation charts incorporating a PEWS scoring tool and escalation guide, promotion of effective communication using the national standard (ISBAR communication tool for patient deterioration), timely nursing and medical input, and clear documentation of management plans. Objectives: I-PEWS was developed to improve prevention, recognition and response to children at risk of inpatient clinical deterioration in Ireland. For a defined period, national implementation was overseen by a Working Group of stakeholders and supported by a National Coordinator. Implementation strategy: Over a three-year period, we piloted and refined the PEWS charts and associated education resources and facilitated national implementation of the Irish PEWS in 29 public hospitals. We developed a centrally-delivered, standardised training programme to establish hospital-level PEWS Trainers. Locally nominated PEWS Leads and Trainers were supported by regular communications, site visits and remote support culminating in a paediatric patient safety celebration day to mark the conclusion of the Working Group and Coordinator involvement. National Key Performance Indicators (KPI) were developed to demonstrate adherence to National Clinical Guideline recommendations by the local governance bodies to include development of locally applicable continuous education standards and regular audit to promote frontline ownership of the change. Results: Implementation of PEWS was challenging due to the number of sites involved and the different specialties, resources and levels of engagement within each. The four quarterly KPI reports from 2018 demonstrate inconsistency in implementation and embedding of PEWS. 21 of 29 (72%) hospitals overall report full compliance with the standards set out in the KPI suite. Issues include (ranges indicate variance in reporting across quarters): no local governance group (33%) no provision for continuous education programme for nurses (1–4 hospitals) or doctors (3–5 hospitals) all admitted children are not monitored using PEWS (1–2 hospitals) audit practices are not as recommended (1–3 hospitals) outcome data is not being collected (4–6 hospitals) Learning: Implementing a national QI initiative is complex. The flexibility for locally relevant adaptations is essential for applicability and buy-in. The KPI data demonstrates a deficit in implementation standards and should be addressed by the Irish health service.